Preclinical safety studies of enadenotucirev, a chimeric group B human-specific oncolytic adenovirus - Illingworth, S; Di, Y; Bauzon, M; Lei, J; Duffy, M; Alvis, S; Champion, B; Lieber, A; Hermiston, T; Seymour, L; Beadle, J; Fisher, K (Elsevier, 2017)
Enadenotucirev is an oncolytic group B adenovirus identified by a process of bio-selection for the ability to selectively propagate in and rapidly kill carcinoma cells. It is resistant to inactivation by human blood components, potentially enabling intravenous dosing in patients with metastatic cancer. However, there are no known permissive animal models described for group B adenoviruses that could facilitate a conventional approach to preclinical safety studies. In this manuscript, we describe our tailored preclinical strategy designed to evaluate the key biological properties of enadenotucirev. As enadenotucirev does not replicate in animal cells, a panel of primary human cells was used to evaluate enadenotucirev replication selectivity in vitro, demonstrating that virus genome levels were >100-fold lower in normal cells relative to tumor cells. Acute intravenous tolerability in mice was used to assess virus particle-mediated toxicology and effects on innate immunity. These studies showed that particle toxicity could be ameliorated by dose fractionation, using an initial dose of virus to condition the host such that cytokine responses to subsequent doses were significantly attenuated. This, in turn, supported the initiation of a phase I intravenous clinical trial with a starting dose of 1 × 10(10) virus particles given on days 1, 3, and 5.